2004
DOI: 10.1021/bi0487140
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies Suggest a Role for α-Synuclein in the Phosphatidylinositol Lipid Signaling Pathway

Abstract: Alpha-synuclein plays a key role in the pathogenesis of many neurodegenerative diseases. To date, its cellular role has yet to be determined, although it has been proposed to be connected to calcium and G protein-mediated dopamine signaling. Alpha-synuclein is known to bind strongly to model membrane surfaces where it may interact with other membrane-associated proteins. Here, we find that the membrane association of alpha-synuclein is enhanced by the presence of phosphatidylinositol 4,5-bisphosphate [PI(4,5)P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 51 publications
5
53
0
Order By: Relevance
“…These structural similarities suggest that ␣-synuclein could serve as an intracellular functional equivalent of apolipoproteins in the brain and so similarly may function in binding and intracellular transport of lipids, stabilizing membranes, and regulating lipid metabolism. Results to support this hypothesis include the observations that ␣-synuclein alters both phospholipase C and D activities in vitro, while its inhibitory effect on phospholipase D may be regulated by ␣-synuclein phosphorylation (31,49,52). Additionally, ␣-synuclein binds to phospholipid vesicles containing stored triglycerides in cultured cells and protects them from hydrolysis (12), suggesting that ␣-synuclein may have a role in stabilizing lipid membrane.…”
mentioning
confidence: 71%
“…These structural similarities suggest that ␣-synuclein could serve as an intracellular functional equivalent of apolipoproteins in the brain and so similarly may function in binding and intracellular transport of lipids, stabilizing membranes, and regulating lipid metabolism. Results to support this hypothesis include the observations that ␣-synuclein alters both phospholipase C and D activities in vitro, while its inhibitory effect on phospholipase D may be regulated by ␣-synuclein phosphorylation (31,49,52). Additionally, ␣-synuclein binds to phospholipid vesicles containing stored triglycerides in cultured cells and protects them from hydrolysis (12), suggesting that ␣-synuclein may have a role in stabilizing lipid membrane.…”
mentioning
confidence: 71%
“…Thus, the synucleins may be involved in the regulation of vesicle recycling and in the maintenance of dopamine homeostasis. A link with inositol-mediated intracellular calcium signalling was recently established when it was shown that aS binds with high affinity to membranes containing phosphatidylinositol-4,5-bisphosphate and that it modulates the activity of phospholipase-Cb [133]. Regarding the critical role of calcium signalling in central cellular events, such as vesicle trafficking and dopamine uptake, this finding deserves further research to elucidate its meaning within the framework of synaptic neurotransmission.…”
Section: Lipid Binding In Vivo and In Cultured Cellsmentioning
confidence: 90%
“…[16][17][18] In addition, the protein exhibits an inhibitory activity of phospholipase D both in vitro and in vivo, indicating a role in lipid-mediated signal transduction. 19 α-Syn seems to interact with unsaturated and polyunsaturated fatty acids (PUFAs), but whether this interaction involves free FAs, as in the case of FA binding proteins 20 or micelles, 21,22 has not been elucidated yet. This interaction promotes the oligomerization of α-syn.…”
mentioning
confidence: 99%